EKSTRAKSI CITRA PADA PROSES KEAMANAN KRIPTOGRAFI MEMANFAATKAN ALGORITMA SECURE HASH (SHA) - ACHMAD FAUZI (STMIK KAPUTAMA, 2020)
The development of increasingly sophisticated information and communication technology is inseparable from the growing importance of long distance communication. Current information exchange is not only in the form of text, but can also be in the form of images. All that can be done using an internet connection. With this internet connection, you can connect with many people. Cryptography aims to prevent images from being seen by unauthorized persons so that information stored on a computer is safe or sent through an internet connection. And can protect the confidentiality of the image from various threats that arise. SHA-256 is one of the hashing functions that is safe enough to be used to transform a byte of data into a hash string. The system built has been able to implement the SHA 256 algorithm which can change the original image file in the form of unknown files and encrypted images that cannot be known, unless read using an application that has been built. the image when encrypted and reused when decrypted with as many as 45 characters and may be in the form of numbers or letters. The SHA 256 process when encrypted is only one cycle, can be played with decryption.